Randomized controlled trial comparing endoscopic ligation with or without sclerotherapy for secondary prophylaxis of variceal bleeding. Issue 1 (January 2016) - Chen, Jie; Zeng, Xiao-qing; Ma, Li-li; Li, Bing; Tseng, Yu-Jen; Lian, Jing-jing; Gao, Hong; Wang, Jian; Luo, Tian-cheng; Chen, Shi-yao
Abstract : Objectives: A recently published network meta-analysis showed that ligation combined with sclerotherapy might be the most efficacious intervention for secondary prophylaxis of variceal bleeding. Most studies excluded patients with concomitant gastric varices; thus, the outcomes in such patients have not yet been reported. The present study aimed to investigate the efficacy of two endoscopic procedures for secondary prophylaxis in cirrhotic patients presenting with both esophageal and gastric varices. Materials and methods: A randomized controlled study was carried out in a tertiary care referral center. Patients were randomized into two groups: sclerotherapy− and sclerotherapy+ group. Continued endoscopic ligation was used to treat esophageal varices in the sclerotherapy− group, whereas combined ligation and sclerotherapy with lauromacrogol was performed in the sclerotherapy+ group. A cyanoacrylate injection was used for gastric varices in both groups. All participants were followed up for 6 months. Results: Overall, 96 patients were included between 25 March 2012 and 25 June 2013. Three patients were lost during follow-up (one in the sclerotherapy− group and two in the sclerotherapy+ group). The cumulative recurrence rate of bleeding was significantly higher in the sclerotherapy+ group (14.6 vs. 35.4%, P =0.013). The cumulative mortality rate (2.1 vs. 6.3%, P =0.286) and the incidence rate of adverse events were similar between the two groups. Conclusion: Continued ligation+cyanoacrylate injection was superior to combined ligation and sclerotherapy+cyanoacrylate injection during the first 6 months in terms of rebleeding in cirrhotic patients presenting with both esophageal and gastric varices. Long-term results entail further investigation (http://www.clinicaltrials.gov, NCT01592578).